Machines, power and the ancient economy - Wilson, A (2002)
This paper examines the relationship between the design and use of mechanical technology, patronage and investment, and economic return, using three main case studies: water-lifting devices, the water-powered grain mill, and the diverse uses of water-power in mining. Water-power was used on a wide scale and in diversified forms at an early date (by the first century A. D.), and the use of mechanical technology to perform economically critical work had an important impact on economic performance and the potential for per capita growth, especially in the latter centuries B. C. and the first two centuries A. D. Conversely, in the third century A. D. the cessation of the employment of hydraulic mining techniques enabling large-scale extraction of gold and other metals may have had an adverse impact on the economy as a whole. Growth and progress do not necessarily follow a linear pattern of advance; technologies are lost as well as adopted.